2018
DOI: 10.6018/eglobal.17.3.289541
|View full text |Cite
|
Sign up to set email alerts
|

Ansiedade em técnicos de enfermagem da atenção básica

Abstract: Objetivo: Evaluar el nivel de ansiedad en el personal de enfermería de la Estrategia Salud de la Familia, con énfasis en los aspectos clave para la aparición de la ansiedad.<br />Método: Estudio descriptivo, enfoque cuantitativo transversal, constituido por 28 técnicos de enfermería, mediante el Inventario de Ansiedad Traço-Estado (IDATE) como una herramienta para la recolección de datos.<br />Resultados: 8 técnicos de enfermería mostraron niveles de alta ansiedad alta 20 baja ansiedad. Hubo un aum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…A segunda tem relação com a personalidade, logo investiga como geralmente o trabalhador considera seu nível de ansiedade. Nota-se que a AE pode variar em intensidade, podendo apresentar nível alto em um determinado momento e em outro não, enquanto a AT é caracterizada por ser mais estável (Fernandes, Chaves Neto, Trajano & Braga, 2018b). Deste modo, durante a aplicação das escalas de ansiedade os trabalhadores referem não estarem ansiosos, logo nível baixo de AE.…”
Section: Resultsunclassified
“…A segunda tem relação com a personalidade, logo investiga como geralmente o trabalhador considera seu nível de ansiedade. Nota-se que a AE pode variar em intensidade, podendo apresentar nível alto em um determinado momento e em outro não, enquanto a AT é caracterizada por ser mais estável (Fernandes, Chaves Neto, Trajano & Braga, 2018b). Deste modo, durante a aplicação das escalas de ansiedade os trabalhadores referem não estarem ansiosos, logo nível baixo de AE.…”
Section: Resultsunclassified
“…In the literature that has emerged during the COVID-19 pandemic, there has been research on the anxiety experienced by health care professionals in hospital settings (Bahadır-Yılmaz & Yüksel, 2020;Çelmeçe & Menekay, 2020;Labrague & de Los Santos, 2020;Milgrom et al, 2020). However, the literature review conducted as part of this study revealed that there are only a limited number of studies specifically analysing the anxiety levels of nurses in primary health care services (Alves Fernandes et al, 2018;Lockwood, 2019;Muşlu et al, 2012). This lack of information exists despite the fact that anxiety, pain and concern are commonly experienced by primary care nurses due to the physical and mental fatigue caused by the greater performance demands in their work environments (Alves Fernandes et al, 2018;Lockwood, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…However, the literature review conducted as part of this study revealed that there are only a limited number of studies specifically analysing the anxiety levels of nurses in primary health care services (Alves Fernandes et al, 2018;Lockwood, 2019;Muşlu et al, 2012). This lack of information exists despite the fact that anxiety, pain and concern are commonly experienced by primary care nurses due to the physical and mental fatigue caused by the greater performance demands in their work environments (Alves Fernandes et al, 2018;Lockwood, 2019). The relevant literature shows that the anxiety experienced by primary care nurses negatively affects the care they provide (Alves Fernandes et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations